Pennelliiside D, a New Acyl Glucose from Solanum pennellii and Chemical Synthesis of Pennelliisides - Rishni Masimbula; Hiroto Kobayashi; Tenki Nakashima; Yurika Nambu; Naoki Kitaoka; Hideyuki Matsuura (Molecules, 2022)
Acyl glucoses are a group of specialized metabolites produced by Solanaceae. Solanum pennellii, a wild-type tomato plant, produces acyl glucoses in its hair-like epidermal structures known as trichomes. These compounds have been found to be herbicides, microbial growth inhibitors, or allelopathic compounds. However, there are a few reports regarding isolation and investigation of biological activities of acyl glucoses in its pure form due to the difficulty of isolation. Here, we report a new acyl glucose, pennelliiside D, isolated and identified from S. pennellii. Its structure was determined by 1D NMR and 2D NMR, together with FD-MS analysis. To clarify the absolute configuration of the acyl moiety of 2-methylbutyryl in the natural compound, two possible isomers were synthesized starting from β-D-glucose pentaacetate. By comparing the spectroscopic data of natural and synthesized compounds of isomers, the structure of pennelliiside D was confirmed to be 3,4-O-diisobutyryl-2-O-((S)-2-methylbutyryl)-D-glucose. Pennelliiside D and its constituent fatty acid moiety, (S)-2-methylbutanoic acid, did not show root growth-inhibitory activity. Additionally, in this study, chemical synthesis pathways toward pennelliisides A and B were adapted to give 1,6-O-dibenzylpennelliisides A and B.